Clade-specific elemental signatures across an Early Triassic marine fauna pave the way for deciphering the affinities of unidentifiable fossils - Christopher P. A. Smith; Pierre Gueriau; Mathieu Thoury; Sebastian Schöder; Emmanuel Fara; Arnaud Brayard (PLoS ONE, 2025)
In palaeontology, the observation of morphological characters is at the heart of species determination. Nonetheless, since most fossils have undergone considerable morphological loss, distortion, and/or flattening throughout their taphonomic history, the use of visual techniques often remains limited. Complementary approaches such as geochemical analyses or molecular palaeontology are increasingly developed. However, them as well remain limited by the preservation state and diagenetic overprinting of the vast majority of fossils. Based on data obtained by state-of-the-art non-destructive synchrotron micro-X-ray fluorescence (µXRF) major-to-trace elemental mapping of Early Triassic Paris Biota fossils, we show here, at least within a single fossil fauna, the existence of a clade-specific elemental signature. Using complete multi-elemental µXRF spectra instead of elemental quantifications/concentrations, we set a data-formatting protocol that allows us to compare the morphology of the spectra. We then statistically demonstrate the existence of a geochemical discrimination between specimens of different clade despite intra-clade mineralogical variability, and build a “elemental-comparative taxonomic identification” model accordingly. The latter, that goes beyond the simple distinction of tissue nature or type of preservation, is all the more important as it appears to hold the potential to identify some hitherto unrecognizable specimens of the fossil record.